Describing Zoom exhaustion and fatigue in nursing students at a university in South Africa - Waheedha Emmamally; Dorien Wentzel; Petra Brysiewicz (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Online platforms have gained considerable support from students and lecturers post COVID-19, however they are associated with student exhaustion and fatigue.